Study guides

☆☆

Q: How do you factor ax plus bx plus 3a plus 3b?

Write your answer...

Submit

Related questions

3a+ax+3b+bx = 3(a+b)+(a+b)x = (a+b)(3+x)

6a square plus b square

x^3 + ax + 3a + 3x^2 = (x^3 + 3x^2) + (ax + 3a) = x^2(x + 3) + a(x + 3) = (x + 3)(x^2 + a)

x3 + ax + 3a + 3x2 = x (x2 + a) + 3 (a + x2) = x (x2 + a) + 3 (x2 + a) = (x2 + a)(x + 3) Checking the work: x3 + ax + 3x2 + 3a or x3 + 3x2 + 3a + ax = x2 (x + 3) + a (3 + x) = x2 (x + 3) + a (x + 3) = (x + 3)(x2 + a)

a(x + y + z)

ax + ay - AZ = a(x + y - z)

a(x + y - z)

Ax + Bx + C is called an algebraic expression.

x2+bx+ax+ab = x2+ax+bx+ab = x(x+a)+b(x+a) = (x+a)(x+b)

AX + BY is not an equation .AX + BY + C = 0is the general equation for a straight line.

ax + b = 15 or ax + b = -15

(a - b)(x + y)

y = (c - Ax) / (B)

It is a straight line with gradient -A/B and intercept C/B.

Ax + B = Bx + C Ax - Bx = (C - B) x (A - B) = (C - B) x = (C - B) / (A - B)

It is -a/b

2x - 13x + 42 = x +ax + b a + b = 2(x - 6.5x + 21) = 34 = a + b

(x + 2)(a + b)

a function

Ax + Bx + C is not a trinomial!

double-replacement

Double Replacement

A double replacement reaction.

A linear equation.

Yes.